The Ten Royal Virtues and Good Educational Administrators in the 21st century - การะวิโก เพชรธนินทร์ (Journal of Educational Review Faculty of Education in MCU, 2018)
This article discusses the ten royal virtues that can be integrated as the virtues of rulers, leaders, parents and school administrators properly. School executives, teachers, students, students’ parents, students and community members close to the schools should be trained with the ten royal virtues.